IMPROVING THE ABILITY TO READ THE QUR'AN OF EARLY CHILDHOOD THROUGH THE APPLICATION OF THE UMMI METHOD IN EARLY CHILDHOOD - Khairunnisa, Eka Setiawati, Hadi Sutiawan (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This study aims to improve the ability to read the Qur'an through the Ummi method in early childhood at Mutiara Insan PAUD, and to evaluate the effectiveness of the application of the method. The population in this study consisted of 12 children aged 5-6 years. Data were collected using observation and documentation techniques. The results showed that the use of the Ummi method succeeded in improving the ability to read the Qur'an in early childhood. This method is applied in a way that children are asked to imitate letters repeatedly until they memorize, after which they are given the opportunity to read one by one. In addition to improving reading skills, the application of the Ummi method also succeeded in building children's self-confidence, making the classroom atmosphere more fun, and increasing their learning motivation. These findings indicate that the Ummi method can be an effective alternative in teaching reading the Qur'an at the early childhood education level, and provide recommendations for the application of this method in other educational institutions, children feel happy and appear active, so the atmosphere in the classroom becomes cool and the quality of learning outcomes is getting better